Strategi Pembukuan Dan Penyusunan Laporan Keuangan UMKM Nizam Jaya - Muhammad Zidan Al Aziz Rahmatullah; Resanda Putra Sulistiono; Ihtadat Alam Makarima Mainun; Fitri Destriani; Mayga Putri Shabella; Mu’tasim Billah (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Financial bookkeeping in Micro, Small, and Medium Enterprises (MSMEs) in rural areas is crucial to effectively manage finances and improve the quality of financial reports. However, many MSMEs operators are reluctant to engage in financial bookkeeping due to perceiving it as a cumbersome process. Nizam Jaya is one of the MSMEs located in the Ngampungan Village, Bareng District, Jombang Regency, and it specializes in banana chips production. Nizam Jaya faces challenges in promoting their business through word-of-mouth and using traditional and manual bookkeeping methods. Hence, the students of the Community Service Program (KKN) Thematic 5 conducted a bookkeeping awareness campaign using an easily understandable approach for the villagers. The aim of this service is to assist Nizam Jaya in improving their bookkeeping practices, maintaining price stability, increasing sales, and introducing their banana chips product to the broader market.